2019
DOI: 10.1002/ece3.5771
|View full text |Cite
|
Sign up to set email alerts
|

Creosote growth rate and reproduction increase in postfire environments

Abstract: Human activities are changing patterns of ecological disturbance globally. In North American deserts, wildfire is increasing in size and frequency due to fuel characteristics of invasive annual grasses. Fire reduces the abundance and cover of native vegetation in desert ecosystems. In this study, we sought to characterize stem growth and reproductive output of a dominant native shrub in the Mojave Desert, creosote bush (Larrea tridentata (DC.) Coville) following wildfires that occurred in 2005. We sampled 55 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…However, L . tridentata 's ability to at least occasionally resprout and grow comparatively fast (Molinari et al 2019) could account for more resilience in the Larrea than in the Coleogyne community. Coleogyne ramosissima lacks resprouting capability, forms minimal persistent soil seed banks, is a temporally irregular mast‐seeder dependent on abundant seed‐producing adults, exhibits minimal seed dispersal, grows slowly (often only 0.5–1 cm in height/yr), and may rely on a “seedling bank” readily destroyed by fire (Pendleton et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, L . tridentata 's ability to at least occasionally resprout and grow comparatively fast (Molinari et al 2019) could account for more resilience in the Larrea than in the Coleogyne community. Coleogyne ramosissima lacks resprouting capability, forms minimal persistent soil seed banks, is a temporally irregular mast‐seeder dependent on abundant seed‐producing adults, exhibits minimal seed dispersal, grows slowly (often only 0.5–1 cm in height/yr), and may rely on a “seedling bank” readily destroyed by fire (Pendleton et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These studies found reduced woody plant abundance following prescribed burns in most cases, 55,[58][59][60] but woody regeneration and interactions with grass species were variable depending on the fire season, fire return interval, and the degree of livestock grazing. 21,34,[61][62][63] Fire rather than livestock grazing may have a larger role in maintaining grass dominance in the border region, although the mechanisms behind the balance of woody plants and grasses remain controversial. 56 Reductions in woody plant cover had a positive effect on wildlife species requiring more open and grass-dominated habitat, but negative effects on wildlife species requiring a higher density of woody vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…4). This may be partially due to N inputs from the re itself or competition release of soil resources related to re-related losses of native shrubs or a combination of the two (Horn et al, 2015, Molinari et al, 2019. These results suggest that red brome is perpetuated through post-re enrichment of inorganic N, which may have important implications for increasing ne fuel continuity that drives invasive grass re cycles in desert ecosystems.…”
Section: Fire Effects On Soils Resource Gradients and Red Brome Produ...mentioning
confidence: 91%